The efficacy of tobramycin pellet as a local drug delivery in the treatment of osteomyelitis - Mohd Yusof, Nazri (2013)
Purpose: The aim of this study is to evaluate the effectiveness of tobramycin pellet (OSTEOSET ® T) in eradicating osteomyelitis of long bone. Design: Retrospective case series Setting: Advance trauma and Limb reconstruction Unit, Dept of Orthopaedic, HTAA Patients/ participants: Patient treated for osteomyelitis of long bone in Advance trauma and Limb reconstruction Unit Intervention: Debridement of infected soft tissue and bone, insertion of calcium sulphate pellet, direct wound closure or with local flaps, external fixation followed by bone grafting or bone transport. Main outcome measures: The primary outcome is eradication of infection. Secondary outcomes include fracture union, Enneking functional score and Lower Extremity Functional Scale. Results: Twelve patients (80%) achieved control of infection. Three patients’ undergone repeated debridement because of persistent serous discharge. In one patient the infection was due to retained implant and repeated culture grew MRSA. Two patients had inadequate resection and repeated culture also grew MRSA in one of them and the other did not grow any organism. Conclusion: Tobramycin pellet is effective adjuvant therapy for osteomyelitis. However, aggressive debridement is still mandatory to achieve control of infection. Significance: Removal of foreign body and adequate debridement are necessary to control osteomyelitis. Tobramycin pellet is useful as adjuvant treatment for osteomyelitis. Local antibiotic delivery was developed to achieve high local concentration of antibiotic while maintaining low level systemic antibiotic levels. It also obliterates dead space that left following resection of osteomyelitic bone